SPH modeling of high velocity impact into ballistic gelatin. Development of an axis-symmetrical formulation. Issue 22 (17th November 2019) - Frissane, H.; Taddei, L.; Lebaal, N.; Roth, S.
ABSTRACT: The investigation of impact biomechanics is of extreme importance in the understanding of damages which are caused by a projectile impacting the human body. In a high-velocity impact framework, nonpenetrating impacts (nonlethal projectiles) or penetrating impacts can both lead to severe body trauma. An interesting way to study these phenomena is the numerical simulation, which can typically bring new information that cannot be accessed with experimental tests. Classical finite element is often used to simulate these kinds of complex problems. However, for perforating impacts, this method can rapidly lead to its limits, especially in terms of grid deterioration, when the projectile goes through the material. An alternative to this problem is to use a meshless method, like Smoothed Particles Hydrodynamics (SPH), which does not involve any mesh of the structure. Thus, the present study proposes to investigate perforating impact in a ballistic gelatin material, which is known as a good biological tissue simulant, using an axisymmetrical SPH code. Axisymmetrical formulation of the problem is developed, using appropriate numerical features such as contact procedure (between the projectile and the material), corrective factors.Experimental tests of the literature involving different impact velocities and different projectile sizes are replicated with the developed code, showing very promising results in terms of penetration and velocity of the projectile in the target.